Religious transhumanism and its critics - Gouw, Arvin ca. 20./21. Jh; Green, Brian P.; Peters, Ted 1941- (Lexington Books, 2022)
"In this book, the contributors examine how various religious traditions engage with transhumanism and its vision for the future"--
Keywords: Transhumanismus; Theologische Anthropologie; Religion; Transhumanism / Religious aspects; Aufsatzsammlung